OPTIMALISASI PENERIMAAN PAJAK DAERAH MELALUI PENINGKATAN KEPATUHAN WAJIB PAJAK DI KABUPATEN INDRAMAYU: Optimization of Local Tax Revenue through Improved Taxpayer Compliance in Indramayu Regency - Siti Jubaedah; Rohadin; Zuki Kurniawan (Jurnal Investasi, 2026)
This study analyzes how the Government of Indramayu Regency seeks to optimize local tax revenue through improving taxpayer compliance, assesses service quality and the role of local government, and identifies the factors affecting taxpayer compliance. The research employs a qualitative descriptive approach. Data were collected through in-depth interviews, observation, and document review involving officials of the Regional Revenue Agency and taxpayers from several local tax categories. The findings show that the local government has pursued tax intensification and extensification, digital payment systems through e-PBB and e-SPTPD, additional payment channels, data updating, and the Bapenda Hits program as a participation stimulus. However, taxpayer compliance remains below expectation. In 2023, active taxpayers accounted for around 42.4 percent and declined to 35.7 percent in 2024, while PBB-P2 compliance fell from 52.5 percent to 43.7 percent. The factors shaping compliance include limited tax knowledge, uneven service quality, low digital literacy, weak perception of tax benefits, taxpayer economic conditions, and inconsistent supervision and sanction enforcement. The study confirms that optimizing local tax revenue cannot rely only on target setting and administrative collection. It requires accessible services, intensive socialization, transparent use of tax revenue, stronger data systems, and cross-agency coordination.